Effects of postoperative nebulized furosemide and budesonide on postoperative sore throat in patients undergoing maxillofacial surgery: A randomized controlled trial - Jie An; Lei Wang; Yuan Chen; Dong Yang; Yan Huang (Elsevier, 2023)
Purpose: Postoperative sore throat (POST) is a common complication. We compared postoperative nebulized furosemide, budesonide, and sodium chloride solution for POST in patients undergoing maxillofacial surgery. Methods: 75 patients were randomly divided into 3 groups. Anesthesia induction and intubation were routinely performed. Following emergence, the patients were randomized to one of three groups. Group F was treated with 40mg of aerosolized furosemide, group B received 2 mg of aerosolized budesonide and Group S was given aerosolized 0.9% sodium chloride solution. Patients were assessed for sore throat,hoarseness, foreign body sensation,dry mouth, cough，nausea and vomiting at 15 min, 1, 2, 4, 6, 8, 12, 24 and 48 h after extubation. Results: Patients all in three groups had comparable clinical and surgical data.Compared to Group S, POST at rest and during swallowing was significantly lower in Group F and Group B at 2, 4, 6, 8 and 12 h (P < 0.05).Compared to Group S, the incidence of postoperative hoarseness was significantly lower in Group F at 1,2,4,6,8,12 h (P < 0.05)and significantly lower in Group B at 6 h and 8 h (P < 0.05). In particular, the incidence of hoarseness at 1,2,4,24 h in group F was significantly lower than that in group B (P < 0.05). In terms of foreign body sensation, group F was significantly lower than group S at 4 h and 6 h(P < 0.05). Conclusions: Postoperative nebulization of furosemide or budesonide are effective ways to reduce the severity of POST. Nebulized furosemide has more advantages in reducing postoperative hoarseness.